Pengaruh Belanja Daerah dan Pertumbuhan Ekonomi Terhadap Kemandirian Keuangan Daerah di Provinsi Jambi - Rahmilna, salwa fadhila; Zamzami, Zamzami; Nurhayani, Nurhayani (Jurusan Akuntansi FEB Universitas Jambi, 2025)
This study aims to analyze the effect of regional expenditure and economic growth on regional financial independence in Jambi Province during the period 2020–2024. The descriptive analysis shows that regional expenditure and economic growth in Jambi Province experienced fluctuations during the study period, particularly due to the impact of the COVID-19 pandemic, but generally indicated a recovery trend. Meanwhile, the level of regional financial independence remains relatively low, as reflected by the high dependence on central government transfers. The regression results indicate that regional expenditure has an effect on regional financial independence, while economic growth also contributes to enhancing fiscal capacity. Simultaneously, both regional expenditure and economic growth influence regional financial independence.